CONTEMPORARY TRENDS IN INTERNATIONAL TOURISM MARKET - Bošković, Tatjana; Mihajlović, Mila (International Journal of Economic Practice and Policy, 2016)
The paper deals with the international tourism market. The aim of the research is to detect the most significant changes and trends both from the perspective of the tourism demand and tourism supply. Global tourism trends have contributed to the emergence and development of selective forms of tourism among which rural tourism occupies an important place.
Keywords: international tourist market; tourism demand; tourist supply; development; selective tourism forms; rural tourism